Feasibility of an Intervention Study to Support Families When Their Loved One Has Life-sustaining Therapy Withdrawn. Issue 1 (February 2021) - Scharf, Barbara; Zhu, Shijun; Tomlin, Sarah; Cheon, Jooyoung; Mooney-Doyle, Kim; Baggs, Judith Gedney; Weigand, Debra
Abstract : This investigation addressed family member perceptions of preparation for withdrawal of life-sustaining treatment in the intensive care unit. These families are at a high risk for psychosocial and physical sequelae. The quantitative results of this mixed methods study are reported. A control group received usual care and an educational booklet component of the intervention. The experimental group received the above plus exposure to comfort cart items and additional psychological support. Twenty-eight family members enrolled over a 13-month period. Sixty-one percent (10 intervention, 7 control) completed the follow-up. Fourteen family members (82%) recalled the booklet. Some family members reported moderate to severe depression (12.5%), anxiety (12.5%), and stress (12.6%). Satisfaction with care (83.7%-85.2%) and family member well-being (44.1) were within the norm. Short Form-36 physical component score was higher than the norm, and the mental component score was lower than the norm. This study demonstrated feasibility and acceptability of the interventions and follow-up questionnaires when families make the difficult decision to withdraw treatment. Strategies are suggested to strengthen statistical power.